O fazer e o refazer do caminho: uma leitura miticossimbólica da obra Ana Z., aonde vai você? de Marina Colasanti - Santana, Jailma Sirino (2020)
The present study has as main objective make a mythical-symbolic analysis of Marina Colasanti’s story Ana Z. Aonde vai você? Considering the actions of the main character Ana Z, the symbolic objects and equally symbolic language that seem to be part of the character’s narrative cycle of departure and return when she searches for identity, resembling the hero myth established by Joseph Campbell. The hero mythical journey that begins with the motivation of the departure, followed by the passage through the threshold of the two worlds, in which he has to overcome several events along the way to win a ‘trophy’, and so, she must return to the beginning place, it is present in several literatures. To set our proposal, we will be supported by Mircea Eliade (2004) and Joseph Campbell (2007), in addition to the studies of E. Mielietinski (1987). We are also supported by Nelly Novaes Coelho (2012) and her studies about myth and symbolic language in children literature. And according to that theoretical support, we try to do a dialogue about some unconsciousness aspects studied by Carl Jung. We obtained the results through a simultaneous interpretation of work and theory, presenting the narrative and pointing which phases of the Hero’s Journey are – or not -presents in Ana Z. Aonde vai você?